Surface treatment method for cemented carbide inserts

CN122644587BActive Publication Date: 2026-10-20CHONGYI ZHANGYUAN TUNGSTEN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611144621.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-20
Estimated Expiration
2046-07-30

AI Technical Summary

Technical Problem

[0005]针对上述问题,本申请提供了一种硬质合金刀片的表面处理方法,旨在解决传统喷砂工艺刃口易掉角、粗糙度不可控、处理均匀性差的技术问题,并协同实现抑制表面氧化、提升焊接锚固强度的附加价值

Benefits of technology

1、创新运用级配刚玉砂、分段变频振动与刃口软胶防护协同体系,将刀片表面粗糙度稳定控制在Ra0.9μm以上的目标区间内,显著提升焊接抗剪强度;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of powder metallurgy, and particularly relates to a surface treatment method of a hard alloy blade, which comprises the following steps: coating a detachable soft glue on a cutting edge of the hard alloy blade; mixing the hard alloy blade, graded corundum sand and a protective liquid containing an antioxidant and an organic viscosity reducer to carry out segmented variable-frequency vibration under a protective gas atmosphere; and then carrying out passivation to obtain a finished blade. By using a graded corundum sand, segmented variable-frequency vibration and cutting edge soft glue protection collaborative system, the surface roughness of the blade is controlled to be greater than Ra0.9 mu m, the welding shear strength is significantly improved, the cutting edge corner defect is effectively eliminated, and the yield rate can be greater than 99%; and by the cooperation of the protective gas atmosphere and the special protective liquid containing the antioxidant, the surface oxidation resistance of the blade is improved, the blade without stress concentration and oxidation and with uniform roughness is prepared, and the application potential of the blade in the heavy cutting welding tool field is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of powder metallurgy technology, specifically a surface treatment method for cemented carbide cutting tools. Background Technology

[0002] Cemented carbide is a high-strength, wear-resistant alloy material made from tungsten carbide as the hard phase and cobalt as the binder phase, produced through powder pressing and high-temperature sintering. It is widely used in cutting tools, drilling tools, and wear-resistant structural components, and is a key basic material in the equipment manufacturing field. Cemented carbide brazed inserts rely on brazing to bond with the tool holder, and have strict requirements for weld surface roughness, surface cleanliness, and cutting edge integrity. Appropriate surface roughness increases the solder spreading area and forms a mechanical anchoring structure, directly determining the weld strength and reliability.

[0003] The industry commonly uses corundum abrasive blasting to roughen the weld surface to meet subsequent welding and assembly requirements. Corundum abrasive blasting relies on high-pressure airflow to drive abrasive particles to impact the workpiece surface. The pressure control window is narrow; excessive pressure can cause fatal defects such as chipping, corner breakage, and micro-cracks, while insufficient pressure results in inadequate surface roughness and an inability to form an effective anchoring structure. Blasting requires individual placement and multiple flipping of the inserts, making the process cumbersome, labor-intensive, and inefficient for mass production. Different sizes and shapes of inserts require specialized fixtures; small-sized and irregularly shaped inserts are difficult to clamp, leading to problems such as missed areas, excessive impact, and uneven roughness, resulting in poor product consistency and low yield. Insufficient roughness results in weld bonding relying solely on metallurgical bonding, with weak mechanical interlocking, leading to incomplete welds, detachment, and premature failure. Excessive roughness creates sharp protrusions on the surface, which, under the combined effects of welding thermal stress and cutting impact stress, can become crack initiation points, causing insert cracking and weld fracture.

[0004] Therefore, developing a surface treatment method for cemented carbide welded cutting inserts that is non-damaging to the cutting edge, has precise and controllable roughness, uniform processing, and is suitable for mass production is of great significance for improving the reliability of tool welding, extending service life, and reducing production costs. Summary of the Invention

[0005] To address the aforementioned issues, this application provides a surface treatment method for cemented carbide cutting tools, aiming to solve the technical problems of easy edge chipping, uncontrollable roughness, and poor uniformity in traditional sandblasting processes, and to synergistically achieve the added value of inhibiting surface oxidation and improving welding anchoring strength.

[0006] This application discloses a surface treatment method for cemented carbide cutting tools, comprising the following steps: S1. Obtain a cemented carbide cutting tool, corundum abrasive, and a protective liquid. The volume ratio of the corundum abrasive to the cemented carbide cutting tool is (2.2~2.8):1. The protective liquid is prepared from an antioxidant, grinding fluid, organic anti-sticking agent, and pure water. S2. Apply peelable soft adhesive to the cutting edge of the carbide blade; S3. Under a protective gas atmosphere, the coated carbide cutting tool, the corundum sand and the protective liquid are mixed and subjected to a first vibration, and then the frequency is reduced to perform a second vibration. S4. The vibrated carbide cutting tool is passivated to obtain the finished cutting tool.

[0007] In the above technical solution, by mixing carbide cutting tools, graded corundum abrasive, and a protective liquid containing antioxidants and organic anti-sticking agents, and then subjecting the mixture to segmented frequency-modulated vibration followed by passivation, a welding cutting tool with suitable roughness and high welding anchoring strength can be obtained. Corundum abrasive directly affects the surface roughness of the carbide cutting tool. Using a blend of 60-mesh and 120-mesh corundum abrasive particles during vibration grinding balances roughening efficiency and surface homogenization. The large-diameter 60-mesh corundum abrasive provides impact to create anchoring grooves, while the small-diameter 120-mesh corundum abrasive fills the gaps and levels the surface, resulting in better grinding uniformity and stable, controllable surface roughness of the finished product. Simultaneously, the volume ratio of corundum abrasive to carbide cutting inserts must be strictly controlled within the range of (2.2~2.8):1. If there is too little corundum abrasive, it will not provide sufficient grinding during vibration; if there is too much corundum abrasive, it will cause excessive impact during vibration, damaging the cutting edge. The protective fluid contains antioxidants, grinding fluid, and organic anti-sticking agents, which simultaneously achieve the triple functions of anti-oxidation, lubrication, and anti-sticking. The organic anti-sticking agent can reduce the viscosity of the protective fluid, break up agglomerated corundum abrasive, and prevent the abrasive from adhering to the cutting edge surface, causing uneven grinding. Applying a peelable soft adhesive coating to the cutting edge before vibration can protect the edge and greatly reduce problems such as chipping, corner breaking, and micro-cracks that occur during vibration. Because carbide cutting inserts are made of sintered tungsten carbide and cobalt powder, the material is hard and brittle, and the welded surface and thin-walled cutting edge are sensitive to continuous impact stress. High-frequency vibration can create an anchoring morphology on the weld surface using corundum abrasive impacts. However, prolonged high-frequency impacts can create sharp peaks and valleys on the surface, creating a risk of stress cracking. Low-frequency vibration can gently polish protruding areas and smooth out surface unevenness. Therefore, in this application, during vibration, a higher frequency is used in the first stage to construct microscopic anchoring grooves, and a lower frequency is used in the second stage to homogenize the surface and eliminate stress concentration. Without segmented vibration, single high-frequency machining would cause severe stress concentration, while single low-frequency machining would fail to achieve the target roughness. Applying a protective gas during vibration can inhibit cobalt phase oxidation, thereby enhancing the cutting tool's oxidation resistance. Passivating the cutting tool after vibration is to isolate it from air and prevent the highly reactive cutting tool surface from re-oxidizing after grinding.

[0008] Furthermore, the cemented carbide cutting tool is prepared by the following method: mixing 92wt%~97wt% of tungsten carbide and the balance cobalt powder, pressing and sintering to obtain the cemented carbide cutting tool, wherein the tungsten carbide has a Fisher particle size of 2~3μm and the surface roughness Ra of the cemented carbide cutting tool is 0.68~0.78μm; Furthermore, the sintering temperature is 1410~1470℃, and the time is 90~100min; Tungsten carbide inserts with a Fisher particle size of 2-3 μm sintered at 1410-1470℃ for 90-100 min exhibit stable performance and moderate surface density. If the tungsten carbide particle size is below 2 μm, the surface of the sintered insert will be too dense, increasing the difficulty of grain coarsening; if it is above 3 μm, surface uniformity will decrease, affecting the stability of the weld bond. Sintering temperatures below 1410℃ will result in insufficient surface density and low strength; temperatures above 1470℃ will easily lead to grain coarsening and increased brittleness. Too short a sintering time results in incomplete sintering, while too long a time provides no additional benefit and increases energy consumption.

[0009] Furthermore, the volume ratio of 60-mesh to 120-mesh particles in the corundum sand is (6.5~7.5):(2.5~3.5); If the proportion of 60-mesh coarse sand particles is too high, sharp peaks and valleys are easily generated on the blade surface, stress concentration occurs, and the cutting edge is prone to chipping; if the proportion of 60-mesh coarse sand particles is too low, the blade surface roughness is insufficient, the welding strength drops sharply, and the yield rate is insufficient.

[0010] Furthermore, the mass ratio of the antioxidant, the grinding fluid, the organic anti-tack agent, and the pure water in the protective liquid is (0.09~0.11):(0.45~0.55):(0.09~0.11):(90~110), and the organic anti-tack agent includes polyethylene glycol, fatty alcohol polyoxyethylene ether, or glycerin; The special protective fluid prepared by using the above proportions of antioxidants, grinding fluid, organic anti-sticking agents and pure water can better inhibit the oxidation of the cutting tool surface during vibration, and the lubrication and anti-sticking materials are also better. Deviation of the proportions will lead to accelerated oxidation of the cutting tool, insufficient roughness or surface contamination.

[0011] Furthermore, the volume ratio of the protective liquid to the corundum sand is 1:(3~5).

[0012] Furthermore, the frequency of the first vibration is 45~55Hz and the duration is 8~12h; the frequency of the second vibration is 25~35Hz and the duration is 12~18h. If the vibration frequency is too high, the blade edge is easily damaged; if it is too low, the homogenization effect is poor. Insufficient vibration time can easily lead to substandard blade surface roughness, while excessive vibration time can easily form sharp peaks and valleys.

[0013] Furthermore, the pressure of the protective gas atmosphere is 0.02~0.05MPa, and the gas used is nitrogen.

[0014] Furthermore, in step S4, the vibrated cemented carbide cutting tool is passivated using a passivation liquid, which includes sodium molybdate-based water-based passivation liquid or sodium tungstate-based water-based passivation liquid, and the passivation time is 3-5 minutes. The sodium molybdate-based passivation solution uses sodium molybdate as the main film-forming agent, citric acid as the chelating agent, and deionized water as the solvent, and is used for immersion at room temperature. The sodium tungstate-based passivation solution uses sodium tungstate as the main film-forming agent, citric acid as the chelating agent, and deionized water as the solvent. During passivation, the cemented carbide cutting tool is simply immersed in the passivation solution at room temperature. If the passivation time is too short, the passivation will be insufficient, and the surface activity of the cutting tool will be unstable; if the passivation time is too long, the wettability will decrease, affecting the welding effect.

[0015] Furthermore, the surface roughness Ra of the finished blade is not less than 0.9 μm, the oxidation rate is not higher than 0.2%, the welding shear strength is not less than 270 MPa, and the yield is not less than 99%.

[0016] Only finished blades that simultaneously meet the following four conditions—surface roughness, oxidation rate, weld shear strength, and are free from edge chipping, breakage, and micro-cracks—can be considered qualified products. Any blade that fails to meet any of these conditions or has surface damage will be deemed defective.

[0017] This application proposes a surface treatment method for cemented carbide cutting tools, which produces the following beneficial effects: 1. By innovatively applying a synergistic system of graded corundum sand, segmented frequency vibration and edge soft rubber protection, the surface roughness of the blade is stably controlled within the target range of Ra0.9μm or higher, significantly improving the shear strength of the weld. 2. By simply controlling the cutting edge coating, corundum sand gradation, and vibration parameters, the chipping defect of the cutting edge can be effectively eliminated, and the product yield can be increased to over 99%. 3. The synergistic effect of a slightly positive pressure protective gas atmosphere with a special protective liquid containing antioxidants can improve the oxidation resistance of the blade surface and keep the blade oxidation rate at a low level. 4. Stress-free, oxidation-free, and uniformly roughened cemented carbide welding inserts were prepared, enhancing their application potential in the field of heavy-duty welding tools. Detailed Implementation

[0018] The technical solutions in the embodiments will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0019] This application discloses a surface treatment method for cemented carbide cutting tools, comprising the following steps: S1. Obtain carbide cutting tools, corundum abrasive, and protective liquid. The volume ratio of corundum abrasive to carbide cutting tools is (2.2~2.8):1. The protective liquid is prepared by antioxidant, grinding fluid, organic anti-sticking agent, and pure water. Preferably, the corundum sand is composed of particles with a particle size of 60 mesh and 120 mesh, wherein the volume ratio of 60 mesh to 120 mesh particles is (6.5~7.5):(2.5~3.5); the mass ratio of antioxidant, grinding fluid, organic anti-sticking agent and pure water in the protective liquid is (0.09~0.11):(0.45~0.55):(0.09~0.11):(90~110), and the organic anti-sticking agent includes polyethylene glycol, fatty alcohol polyoxyethylene ether or glycerin; The volume ratio of the protective liquid to the corundum sand is 1:(3~5); In some preferred embodiments of this application, the cemented carbide cutting tool is prepared by the following method: 92wt%~97wt% of tungsten carbide and the balance cobalt powder are mixed, pressed and sintered to obtain a cemented carbide cutting tool with a surface roughness Ra of 0.68~0.78μm, and the tungsten carbide used has a Fisher particle size of 2~3μm; the sintering temperature is 1410~1470℃ and the time is 90~100min.

[0020] S2. Apply peelable soft rubber to the cutting edge of the carbide blade; In some preferred embodiments of this application, the thickness of the peelable soft adhesive coating is 0.1~0.3μm.

[0021] S3. Under a protective gas atmosphere, the coated carbide cutting tool, corundum sand and protective liquid are mixed and subjected to the first vibration, and then the frequency is reduced for the second vibration. Preferably, the frequency of the first vibration is 45~55Hz and the duration is 8~12h; the frequency of the second vibration is 25~35Hz and the duration is 12~18h; the pressure of the protective gas atmosphere is 0.02~0.05MPa, and the gas used is nitrogen.

[0022] S4. Passivate the vibrated carbide cutting tool to obtain the finished cutting tool. In some preferred embodiments of this application, the cutting tool and abrasive (corundum sand, protective liquid) are first separated by sieving. Then, the cutting tool is cleaned by compressed air. Next, the vibrated cemented carbide cutting tool is passivated for 3-5 minutes using a passivation liquid, which includes sodium molybdate-based water-based passivation liquid or sodium tungstate-based water-based passivation liquid. After being cleaned again, the surface roughness Ra of the finished cutting tool is not less than 0.9 μm, the oxidation rate is not higher than 0.2%, the welding shear strength is not less than 270 MPa, and the yield is not less than 99%.

[0023] The technical solution of this application will be further described below with reference to specific embodiments.

[0024] Example 1

[0025] A surface treatment method for cemented carbide cutting tools includes the following steps: S1. Obtain cemented carbide inserts, corundum sand, and protective liquid. The volume ratio of corundum sand to cemented carbide inserts is 2.5:1, and the volume ratio of corundum sand to protective liquid is 3:1. The mass ratio of antioxidant, grinding fluid, organic anti-sticking agent, and pure water in the protective liquid is 0.1:0.5:0.1:100. Among them, the volume ratio of 60 mesh to 120 mesh particles in the corundum sand is 7:3. The cemented carbide inserts are prepared by the following method: 94wt% tungsten carbide and 6wt% cobalt powder are mixed, pressed, and sintered at 1440℃ for 95min to obtain cemented carbide inserts. The tungsten carbide used has a Fisher particle size of 2μm, and the surface roughness Ra of the cemented carbide inserts is 0.749μm. S2. Apply peelable soft rubber to the cutting edge of the carbide blade; S3. Under a nitrogen atmosphere of 0.03 MPa, the coated carbide cutting tool, corundum sand and protective liquid are mixed and subjected to a first vibration, followed by a second vibration at a reduced frequency. The frequency of the first vibration is 50 Hz and the duration is 10 h; the frequency of the second vibration is 30 Hz and the duration is 15 h. S4. Passivate the vibrated cemented carbide insert with a sodium molybdate-based water-based passivation solution for 4 minutes to obtain the finished insert.

[0026] The finished blade of this embodiment has a surface roughness Ra of 0.974 μm, no chipping, an oxidation rate of 0.12%, a weld shear strength of 285 MPa, and a yield rate of 99.6%. This finished blade is used as a reference sample for weld shear strength.

[0027] Example 2

[0028] A surface treatment method for cemented carbide cutting tools includes the following steps: S1. Obtain cemented carbide inserts, corundum sand, and protective liquid. The volume ratio of corundum sand to cemented carbide inserts is 2.2:1, and the volume ratio of corundum sand to protective liquid is 3:1. The mass ratio of antioxidant, grinding fluid, organic anti-sticking agent, and pure water in the protective liquid is 0.1:0.5:0.1:100. Among them, the volume ratio of 60 mesh to 120 mesh particles in the corundum sand is 7:3. The cemented carbide inserts are prepared by the following method: 97wt% tungsten carbide and 3wt% cobalt powder are mixed, pressed, and sintered at 1410℃ for 100min to obtain cemented carbide inserts. The tungsten carbide used has a Fisher particle size of 2.5μm, and the surface roughness Ra of the cemented carbide inserts is 0.686μm. S2. Apply peelable soft rubber to the cutting edge of the carbide blade; S3. Under a nitrogen atmosphere of 0.03 MPa, the coated carbide cutting tool, corundum sand and protective liquid are mixed and subjected to a first vibration, followed by a second vibration at a reduced frequency. The frequency of the first vibration is 50 Hz and the duration is 10 h; the frequency of the second vibration is 30 Hz and the duration is 15 h. S4. Passivate the vibrated cemented carbide insert with a sodium molybdate-based water-based passivation solution for 4 minutes to obtain the finished insert.

[0029] The finished blade of this embodiment has a surface roughness Ra of 0.928 μm, no chipping, an oxidation rate of 0.13%, a weld shear strength of 271 MPa, and a yield rate of 99.2%. The weld shear strength of this finished blade is 5% lower than that of the reference sample in Example 1.

[0030] Example 3

[0031] A surface treatment method for cemented carbide cutting tools includes the following steps: S1. Obtain cemented carbide inserts, corundum sand, and protective liquid. The volume ratio of corundum sand to cemented carbide inserts is 2.8:1, and the volume ratio of corundum sand to protective liquid is 3:1. The mass ratio of antioxidant, grinding fluid, organic anti-sticking agent, and pure water in the protective liquid is 0.1:0.5:0.1:100. Among them, the volume ratio of 60 mesh to 120 mesh particles in the corundum sand is 7:3. The cemented carbide inserts are prepared by the following method: 92wt% tungsten carbide and 8wt% cobalt powder are mixed, pressed, and sintered at 1470℃ for 90min to obtain cemented carbide inserts. The tungsten carbide used has a Fisher particle size of 3μm, and the surface roughness Ra of the cemented carbide inserts is 0.774μm. S2. Apply peelable soft rubber to the cutting edge of the carbide blade; S3. Under a nitrogen atmosphere of 0.03 MPa, the coated carbide cutting tool, corundum sand and protective liquid are mixed and subjected to a first vibration, followed by a second vibration at a reduced frequency. The frequency of the first vibration is 50 Hz and the duration is 10 h; the frequency of the second vibration is 30 Hz and the duration is 15 h. S4. Passivate the vibrated cemented carbide insert with a sodium molybdate-based water-based passivation solution for 5 minutes to obtain the finished insert.

[0032] The finished blade of this embodiment has a surface roughness Ra of 0.991 μm, no chipping, an oxidation rate of 0.11%, a weld shear strength of 288 MPa, and a yield rate of 99.5%. The weld shear strength of this finished blade is 1% higher than that of the reference sample.

[0033] Example 4

[0034] A surface treatment method for cemented carbide cutting tools includes the following steps: S1. Obtain cemented carbide inserts, corundum sand, and protective liquid. The volume ratio of corundum sand to cemented carbide inserts is 2.8:1, and the volume ratio of corundum sand to protective liquid is 5:1. The mass ratio of antioxidant, grinding fluid, organic anti-sticking agent, and pure water in the protective liquid is 0.1:0.5:0.1:100. Among them, the volume ratio of 60 mesh to 120 mesh particles in the corundum sand is 7:3. The cemented carbide inserts are prepared by the following method: 93wt% tungsten carbide and 7wt% cobalt powder are mixed, pressed, and sintered at 1440℃ for 95min to obtain cemented carbide inserts. The tungsten carbide used has a Fisher particle size of 2.5μm, and the surface roughness Ra of the cemented carbide inserts is 0.735μm. S2. Apply peelable soft rubber to the cutting edge of the carbide blade; S3. Under a nitrogen atmosphere of 0.03 MPa, the coated carbide cutting tool, corundum sand and protective liquid are mixed and subjected to a first vibration, followed by a second vibration at a reduced frequency. The frequency of the first vibration is 50 Hz and the duration is 10 h; the frequency of the second vibration is 30 Hz and the duration is 15 h. S4. Passivate the vibrated cemented carbide insert with a sodium molybdate-based water-based passivation solution for 4 minutes to obtain the finished insert.

[0035] The finished blade of this embodiment has a surface roughness Ra of 0.956 μm, no chipping, an oxidation rate of 0.17%, a weld shear strength of 276 MPa, and a yield rate of 99.3%. The weld shear strength of this finished blade is 3% lower than that of the reference sample.

[0036] Comparative Example 1 The only difference between this comparative example and Example 1 is that in step S1, the volume ratio of corundum sand to cemented carbide cutting tool is 1.8:1, and everything else is exactly the same as in Example 1.

[0037] The test results showed that the surface roughness Ra of the finished cutting tool in this comparative example was 0.883 μm, which is relatively low. It also showed corner chipping, an oxidation rate of 0.14%, a weld shear strength of 219 MPa, and a yield rate of 82.3%. The weld shear strength of this finished cutting tool was 23% lower than that of the reference sample.

[0038] Comparative Example 2 The only difference between this comparative example and Example 1 is that step S2 is omitted, and the carbide cutting tool obtained in step S1 is directly subjected to segmented frequency conversion vibration. Otherwise, it is exactly the same as Example 1.

[0039] The finished cutting tool of this comparative example has a surface roughness Ra of 0.955 μm, has chipped corners, an oxidation rate of 0.13%, a weld shear strength of 273 MPa, and a yield rate of 87.2%. The weld shear strength of this finished cutting tool is 4% lower than that of the reference sample.

[0040] Comparative Example 3 The only difference between this comparative example and Example 1 is that in step S1, the protective liquid does not contain organic viscosity reducers, and the mass ratio of antioxidant, grinding fluid, organic viscosity reducer and pure water is 0.1:0.5:100. Everything else is exactly the same as in Example 1.

[0041] The finished cutting tool of this comparative example has a surface roughness Ra of 0.912 μm, no chipping, an oxidation rate of 0.15%, a weld shear strength of 245 MPa, and a yield rate of 93.5%. The weld shear strength of this finished cutting tool is 14% lower than that of the reference sample.

[0042] Comparative Example 4 The only difference between this comparative example and Example 1 is that nitrogen gas is not used for protection in step S3; otherwise, they are exactly the same as in Example 1.

[0043] The finished cutting tool of this comparative example has a surface roughness Ra of 0.839 μm, no chipping, an oxidation rate of 1.83%, a weld shear strength of 205 MPa, and a yield rate of 91.7%. The weld shear strength of this finished cutting tool is 28% lower than that of the reference sample.

[0044] Comparative Example 5 The only difference between this comparative example and Example 1 is that in step S3, segmented frequency conversion vibration is not performed, but vibration is performed at 50Hz for 25 hours. Otherwise, it is exactly the same as Example 1.

[0045] The finished cutting tool of this comparative example has a surface roughness Ra of 1.127 μm, no chipping, an oxidation rate of 0.12%, a weld shear strength of 208 MPa, and a yield rate of 98.8%. The weld shear strength of this finished cutting tool is 27% lower than that of the reference sample.

[0046] Comparative Example 6 The only difference between this comparative example and Example 1 is that passivation is not performed in step S4; otherwise, they are exactly the same as in Example 1.

[0047] The finished cutting tool of this comparative example has a surface roughness Ra of 0.969 μm, no chipping, an oxidation rate of 0.12%, a weld shear strength of 254 MPa, and a yield rate of 99.5%. The weld shear strength of this finished cutting tool is 11% lower than that of the reference sample.

[0048] Comparative Example 7 The only difference between this comparative example and Example 1 is that in step S1, the particle size of the corundum sand is 60 mesh, and everything else is exactly the same as in Example 1.

[0049] The test results showed that the surface roughness Ra of the finished cutting tool in this comparative example was 1.153 μm, with slight burrs on the cutting edge and local stress concentration. The oxidation rate was 0.13%, the weld shear strength was 228 MPa, and the yield rate was 89.6%. The weld shear strength of this finished cutting tool was 20% lower than that of the reference sample.

[0050] The above description is only a preferred embodiment of this application and does not limit the patent scope of this application. All equivalent structural transformations made using the content of this application's specification under the inventive concept of this application, or direct / indirect applications in other related technical fields, are included within the patent protection scope of this application.

Claims

1. A surface treatment method for cemented carbide cutting tools, characterized in that, Includes the following steps: S1. Obtain a cemented carbide cutting tool, corundum sand, and a protective liquid. The corundum sand is composed of particles with a particle size of 60 mesh and 120 mesh. The volume ratio of the corundum sand to the cemented carbide cutting tool is (2.2~2.8):

1. The protective liquid is prepared by antioxidant, grinding fluid, organic anti-sticking agent, and pure water. S2. Apply peelable soft adhesive to the cutting edge of the carbide blade; S3. Under a protective gas atmosphere, the coated carbide cutting tool, the corundum sand and the protective liquid are mixed and subjected to a first vibration, and then the frequency is reduced to perform a second vibration. S4. The vibrated carbide cutting tool is passivated to obtain the finished cutting tool.

2. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The cemented carbide cutting tool is prepared by the following method: mixing 92wt%~97wt% of tungsten carbide and the balance cobalt powder, pressing and sintering to obtain the cemented carbide cutting tool, wherein the tungsten carbide has a Fisher particle size of 2~3μm and the surface roughness Ra of the cemented carbide cutting tool is 0.68~0.78μm.

3. The surface treatment method for cemented carbide cutting tools according to claim 2, characterized in that, The sintering temperature is 1410~1470℃ and the time is 90~100min.

4. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The volume ratio of 60-mesh to 120-mesh particles in the corundum sand is (6.5~7.5):(2.5~3.5).

5. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The mass ratio of the antioxidant, the grinding fluid, the organic anti-tack agent, and the pure water in the protective liquid is (0.09~0.11):(0.45~0.55):(0.09~0.11):(90~110), and the organic anti-tack agent includes polyethylene glycol, fatty alcohol polyoxyethylene ether, or glycerin.

6. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The volume ratio of the protective liquid to the corundum sand is 1:(3~5).

7. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The frequency of the first vibration is 45~55Hz and the duration is 8~12h; the frequency of the second vibration is 25~35Hz and the duration is 12~18h.

8. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The pressure of the protective gas atmosphere is 0.02~0.05MPa, and the gas used is nitrogen.

9. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, In step S4, the vibrated cemented carbide cutting tool is passivated using a passivation solution, which includes a sodium molybdate-based water-based passivation solution or a sodium tungstate-based water-based passivation solution, and the passivation time is 3-5 minutes.

10. The surface treatment method for cemented carbide cutting tools according to claim 1, characterized in that, The finished blade has a surface roughness Ra of not less than 0.9 μm, an oxidation rate of not more than 0.2%, a weld shear strength of not less than 270 MPa, and a yield of not less than 99%.

Citation Information

Patent Citations

  • Method for reducing surface oxidation rate of hard alloy

    CN116141094A

  • Cutter with submicron diamond coating as well as preparation method and application of cutter

    CN117165913A